Psychological predictors of injury among elite athletes - Galambos, S. A.; Terry, P. C.; Moyle, G. M.; Locke, S. A. (British Journal of Sports Medicine, 2005)
Objectives: To establish injury rates among a population of elite athletes, to provide normative data for psychological variables hypothesised to be predictive of sport injuries, and to establish relations between measures of mood, perceived life stress, and injury characteristics as a precursor to introducing a psychological intervention to ameliorate the injury problem.